PERBEDAAN TEKANAN DARAH DAN DENYUT NADI PEKERJA AKIBAT TEKANAN PANAS DI PENGECORAN LOGAM INDUKSI DAN KUPOLA CV. X KLATEN - Fitria Ardiani; Siswi Jayanti; Suroto Suroto (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Heat stress in metal casting induction and kupola CV.X Klaten exceeds the threshold value according to the regulation of Minister manpower PER.13/MEN/X/2011 is>280C for moderate workload, with setting work time per hour for 75-100%. The purpose of this research is to know difference of blood pressure and pulse rate of workers due to heat stress in metal casting induction and kupola CV.X Klaten. Explanatory research type (to explain) with cross sectional approach.The independent variable is heat stress and the dependent variable is blood pressure and pulse rate. This research measurements using Questemp 34 to hot pressure gauged and digital tensimeter to measure blood pressure and pulse rate. Total sampling of entire population of workers in smelting and metal moulding induction and kupola amounted to 40 workers. Data analysis using univariate analysis and bivariate. The results showed that there is difference of systolic blood pressure, diastolic, arterial, and pulse rate in induction and kupola workers, statistical tests of Independent samples t test obtained (p value 0,017), (p value 0,030), (p value 0,001) and (p value 0,001). Conclusion of this research is normal blood pressure in induction workers a number of 65% from 20 workers, in kupola 55% of 20 workers. Normal pulse rate of induction workers is 80% of 20 workers, in kupola 90% of 20 workers. As a suggestion is provision of health care facilities for workers through cooperative teamwork metal casting business owners with the nearest health service.